Conflict and cooperation in the management of European rabbit Oryctolagus cuniculus damage to agriculture in Spain. Issue 4 (18th October 2020) - Delibes‐Mateos, Miguel; Arroyo, Beatriz; Ruiz, Jorge; Garrido, Fernando E.; Redpath, Steve; Villafuerte, Rafael
Abstract: Conflicts over the management of wildlife species that impact human livelihoods are increasingly frequent. In Spanish farmland areas, the European rabbit, one of the most important game species, can cause considerable crop damage. Tensions typically emerge between farmers who advocate rabbit reduction and hunters who are responsible for controlling populations when crop damage occurs but wish for healthy rabbit populations for shooting. In this study, we used in‐depth interviews and small group discussions with farmers, hunters and representatives of the governmental environmental and agricultural agencies to assess their positions in this conflict. Our results showed tensions between and within groups, and that the conflict is influenced by leadership, distrust and past decision‐making issues, and by differences in beliefs among groups. Positions of farmers and hunters are also relatively rigid, which may make difficult their engagement in collaborative processes. To be effective, such processes would demand that local leaders were empowered and likely also that external neutral mediators were involved. Our study highlights the complexity and dynamic nature of the conflicts associated with wildlife species causing damage to human livelihoods and provides new insights that may be useful to facilitate dialogue and negotiation between stakeholders and to aid management and governance. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.